2023
DOI: 10.1002/med.21960
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neurotrophic factors in the treatment of dementia, stroke and TBI: Effects of Cerebrolysin

Abstract: Neurotrophic factors (NTFs) are involved in the pathophysiology of neurological disorders such as dementia, stroke and traumatic brain injury (TBI), and constitute molecular targets of high interest for the therapy of these pathologies. In this review we provide an overview of current knowledge of the definition, discovery and mode of action of five NTFs, nerve growth factor, insulin‐like growth factor 1, brain derived NTF, vascular endothelial growth factor and tumor necrosis factor alpha; as well as on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 329 publications
(632 reference statements)
0
2
0
Order By: Relevance
“…35 Upon binding to their receptors, neurotrophic factors, such as BDNF, nerve growth factor-activated downstream targets to trigger neuron differentiation, neural proliferation, and synapse formation. 28,36 BDNF abundantly expressed in the hippocampus and front cortex plays a pivotal role in memory and learning. 28 BDNF interacted with TrkB, promoted its autophosphorylation, and activated three major pathways: (1) phosphoinositide-3 kinase (PI-3 K)/Akt, (2) Ras/ raf/mitogen-activated protein kinase (MAPK) pathways, and (3) CREB protein.…”
Section: Nlwe and Q3g Recovered Neurogenesis And Bdnf Downstream Sign...mentioning
confidence: 99%
“…35 Upon binding to their receptors, neurotrophic factors, such as BDNF, nerve growth factor-activated downstream targets to trigger neuron differentiation, neural proliferation, and synapse formation. 28,36 BDNF abundantly expressed in the hippocampus and front cortex plays a pivotal role in memory and learning. 28 BDNF interacted with TrkB, promoted its autophosphorylation, and activated three major pathways: (1) phosphoinositide-3 kinase (PI-3 K)/Akt, (2) Ras/ raf/mitogen-activated protein kinase (MAPK) pathways, and (3) CREB protein.…”
Section: Nlwe and Q3g Recovered Neurogenesis And Bdnf Downstream Sign...mentioning
confidence: 99%
“…Nonetheless, numerous studies on NGF in craniocerebral trauma have demonstrated that administration via different routes produces curative effects without obvious adverse effects. 18 It is hypothesized that the administration of NGF through multiple routes and the use of medications to temporarily access the blood-brain barrier following cerebral trauma can ensure the maintenance of a high level of NGF in damaged brain tissue, thus exerting the neuroprotective effect of NGF. In this study, following HBO therapy, there was an improvement in the condition, and the NGF content saw a more significant increase.…”
Section: Dovepressmentioning
confidence: 99%
“…These cells transform into interneurons and radially migrate to the olfactory bulb (OB) by the rostral migratory stream (RMS) and differentiate into olfactory granule cells (GCs) and periglomerular cells, which integrate into the neuronal circuitry [ 4 , 5 ]. However, it is generally accepted that the proliferation and differentiation of NSCs are influenced by changes of structures in many brain disorders, and new neurons can migrate to impaired regions to facilitate the restoration of neural function, thereby maintaining brain homeostasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%